2019
DOI: 10.37058/jem.v4i1.689
|View full text |Cite
|
Sign up to set email alerts
|

Membangun Keunggulan Bersaing Melalui Inovasi Produk, Inovasi Proses, Inovasi Marketing Dan Inovasi Organisasi Untuk Meningkatkan Kinerja Perusahaan

Abstract: The rife number of Meatball sellers in Tasikmalaya make the business competition increased incisively. The incisive business competition requires business actors to always innovate so that their business can remain sustainable and grow. This research aims to analyze how the influence of product innovation, process innovation, marketing innovation and organizational innovation to competitive advantage and its implication to improvement of company performance. Empirical testing is done in Meatball industry in Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
1
1
Order By: Relevance
“…Husaeni et al (2021) in his research found that the competitive advantage possessed by a company will affect the company's business performance. However, it is different from the research conducted by Bahren et al (2018), who stated that competitive advantage has no effect on business performance. The growth of MSME business performance can be measured by the number of workers, fluctuations in sales, and net profits.…”
Section: Introductioncontrasting
confidence: 83%
“…Husaeni et al (2021) in his research found that the competitive advantage possessed by a company will affect the company's business performance. However, it is different from the research conducted by Bahren et al (2018), who stated that competitive advantage has no effect on business performance. The growth of MSME business performance can be measured by the number of workers, fluctuations in sales, and net profits.…”
Section: Introductioncontrasting
confidence: 83%
“…Inovasi merupakan sebuah ide, praktek, atau obyek yang dipahami sebagai sesuatu yang baru oleh masing-masing individu atau unit pengguna lainnya. Studi tentang inovasi telah dijustifikasi oleh para ahli, praktisi dan pembuat kebijakan bahwa inovasi adalah sumber utama keunggulan kompetitif, perubahan industri dan pertumbuhan ekonomi (Bahren, Ramadhani, & Suroso, 2018).…”
Section: Pendahuluanunclassified